2016
DOI: 10.5032/jae.2016.02106
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Student Cultural Awareness and Perceptions of Different Cultures

Abstract: The population of the United States is growing and increasing in cultural diversity. Of the total U. S. population in 2010, 50.48

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…While the educators did face structural challenges during the course of the partnership and despite the observation that there remained clear tensions between the authentic vs. standardised approaches to writing instruction in the schools, as highlighted earlier, the successes that were indeed observed with literacy seem to align with previous research, pointing to the usefulness of awareness for developing cultural understanding, enhancing relationships and instruction, differentiating instruction, impacting instruction, and providing diverse populations of students with equitable learning opportunities (e.g. Pedersen, ; Schoorman & Camarillo, ; Klug & Hall, ; Pohan & Adams, ; Jones, ; Rodriguez & Lamm, ; Tucker, ; Pallotta, ). The evidence that awareness was reflected within the context of the RPP suggests that more research is needed to determine if and how structural elements of an RPP can facilitate (or disrupt) awareness and influence literacy educators’ responses to CLDs’ literacy practices.…”
Section: Resultsmentioning
confidence: 63%
“…While the educators did face structural challenges during the course of the partnership and despite the observation that there remained clear tensions between the authentic vs. standardised approaches to writing instruction in the schools, as highlighted earlier, the successes that were indeed observed with literacy seem to align with previous research, pointing to the usefulness of awareness for developing cultural understanding, enhancing relationships and instruction, differentiating instruction, impacting instruction, and providing diverse populations of students with equitable learning opportunities (e.g. Pedersen, ; Schoorman & Camarillo, ; Klug & Hall, ; Pohan & Adams, ; Jones, ; Rodriguez & Lamm, ; Tucker, ; Pallotta, ). The evidence that awareness was reflected within the context of the RPP suggests that more research is needed to determine if and how structural elements of an RPP can facilitate (or disrupt) awareness and influence literacy educators’ responses to CLDs’ literacy practices.…”
Section: Resultsmentioning
confidence: 63%
“…Participants focus on their own culture. However, the necessity of considering cultural differences in the teaching process is proved by studies (Parlindungan, Rifai, & Safriani, 2018;Rodriguez & Lamm, 2016). As a result of different cultures and classroom discussions, it was determined that participants rearranged their knowledge in the end-of-day evaluations.…”
Section: Discussion and Conclussionmentioning
confidence: 99%
“…This inaccurate perception of Latinos by such a large portion of the non-Latino population, what Chavez terms the Latino Threat Narrative, helps perpetuate existing structural discrimination practices and mistrust as many associate the portrayal of illegal immigrants in the media with all Latinos. A related study by Rodriguez and Lamm (2016) found agriculture undergraduates' colorblindness was a predictor of their attitudes toward undocumented immigrants. With so much negativity in the media, political climate and education, many Latino students begin to internalize and believe these stereotypes.…”
Section: Introduction and Review Of Literaturementioning
confidence: 94%